Intestinal prolapse through omphalomesenteric fistula, a rare cause of neonatal occlusion: A case report - Cheikh Diouf; Ndeye Aby Ndoye; Aimé Lakh Faye; Oumar Ndour; Gabriel Ngom (Elsevier, 2016)
Acute intestinal obstruction secondary to omphalomesenteric fistula is a very rare condition. Omphalomesenteric fistula is a consequence of a defect in involution of the vitelline duct between the fifth and ninth week of intrauterine development. We are reporting on a case of neonatal intestinal obstruction due to a prolapse of small bowel through an omphalomesenteric fistula. A newborn baby aged 15 days was admitted in emergency with acute intestinal obstruction lasting for two days. The physical examination found prolapse of small bowel through a persistent omphalomesenteric duct. He received surgical treatment with favorable evolution. The scarcity of the reason during the neonatal period should draw the attention of pediatric surgeons because of its potential complications.